Case report: The value of early application of mNGS technology in the diagnosis and treatment of severe Legionnaires’ disease: reports of two cases with different outcomes - Fang, Jianqing; Wang, Zhe; Shen, Yu; Wu, Xuenong; Fang, Hao; Sun, Xiaokui; Yu, Ting; Zhang, Qingqing (Frontiers in Medicine, 2025)
BackgroundLegionnaires’ disease has a high clinical mortality rate, and early diagnosis and treatment are critical. Increasing evidence shows that metagenomic next-generation sequencing (mNGS) has excellent potential for the early identification of pathogens. To help clinicians better recognize Legionnaires’ disease in its early stage and to illustrate the diagnostic value of mNGS technology, we reviewed and summarized two cases of severe Legionnaires’ disease.Methods and analysisWe selected two patients with severe Legionnaires’ disease who were admitted to our department in recent years. We discuss experience with them and the shortcomings in their treatment by summarizing their medical history, disease evolution, tests, and diagnostic and therapeutic processes.ResultsIn both patients, the diagnosis of Legionnaires’ disease was confirmed through analysis of the bronchoalveolar lavage fluid (BALF). The middle-aged male patient was cured and discharged due to early detection and diagnosis. The elderly immunocompromised patient died due to a delay in diagnosis.ConclusionThis study highlights the importance of the early recognition and diagnosis of severe Legionnaires’ disease and the advantages of mNGS in identifying the pathogen.